Combinational PRR Agonists in Liposomal Adjuvant Enhances Immunogenicity and Protective Efficacy in a Tuberculosis Subunit Vaccine - Hao, Ling; Wu, Yaqi; Zhang, Yandi; Zhou, Zijie; Lei, Qing; Ullah, Nadeem; Banga Ndzouboukou, Jo-Lewis; Lin, Xiaosong; Fan, Xionglin (Frontiers in Immunology, 2020)
Bacillus Calmette-Guerin (BCG) is the only licensed vaccine to prevent children from tuberculosis (TB), whereas it cannot provide effective protection for adults. Our previous work showed a novel vaccine candidate, liposomal adjuvant DMT emulsified with a multistage antigen CMFO, could protect mice against primary progressive TB, latency and reactivation. To develop a more effective vaccine against adult TB, we aimed to further understand the role of pattern recognition receptor (PRR) agonists monophosphoryl lipid A (MPLA) and trehalose-6,6’-dibehenate (TDB) of the liposomal adjuvant DMT in the CMFO subunit vaccine-induced protection. Using C57BL/6 mouse models, the current study prepared different dimethyldioctadecylammonium (DDA) based liposomal adjuvants with MPLA, TDB or both (DMT), and then compared the immunogenicity and the protective efficacy among different liposomal adjuvanted CMFO subunit vaccines. Our study demonstrated that CMFO/DMT provided stronger and longer-lasting protective efficacy than the CMFO emulsified with adjuvants DDA or DDA/TDB. In addition, DDA/MPLA adjuvanted CMFO conferred a comparable protection in the lung as CMFO/DMT did. Higher levels of IFN-γ, IL-2, TNF-α and IL-17A secreted by splenocytes were related with a more powerful and durable protection induced by CMFO/DMT through a putative synergistic effect of both MPLA and TDB via binding to TLR4 and Mincle. IL-2+ CD4+ T cells, especially IL-2+ CD4+ TCM cells, in the lung after infection were significantly associated with the vaccine-induced protection, whereas stronger IL-10 response and lower IL-2+ CD4+ T cells also contributed to the inferior protection of the DDA/TDB adjuvanted CMFO subunit vaccine. Given their crucial roles in vaccine-induced protection, combinational different PRR agonists in adjuvant formulation represents a promising strategy for the development of next-generation TB vaccine.